The poetics of stage space : the theory and process of theatre scene design - Bergner, Bruce A., 1962- (McFarland & Company, Inc., Publishers, 2013)
"This book is basically an analysis of theatre scene design through the powers and characteristics of physical space. It covers an array of considerations for the theatre designer: the observable features of given physical spaces, their layout, detailing and atmosphere, present the features from the points of view of various disciplines"--Provided by publisher.